Overview of the teacher's role in instilling student discipline values - Lora, Haditya Aprita (Science Center Group, 2024)
Background: Discipline constitutes a fundamental component of character education and plays a critical role in shaping students’ responsibility, consistency, and adherence to social norms. In secondary education, teachers serve as primary agents in fostering discipline; however, the effectiveness of this role is often influenced by contextual, familial, and socio-environmental factors. Objective: This study aimed to describe teachers’ roles in instilling discipline values among junior secondary school students and to analyze the challenges encountered in implementing character education related to discipline. Methods: A qualitative descriptive design was employed. Ten teachers with a minimum of three years of teaching experience were selected through purposive sampling, along with school principals as key informants. Data were collected through semi-structured interviews and direct classroom observations over a four-month period. Thematic analysis was conducted to identify recurring patterns related to instructional strategies, reinforcement approaches, and contextual barriers. Data credibility was strengthened through triangulation of sources and methods. Results: The findings indicate that teachers primarily instill discipline through role modeling, positive reinforcement, classroom rule establishment, and collaborative discussion. Teachers who consistently demonstrated punctuality, responsibility, and adherence to school regulations were more effective in promoting disciplined behavior among students. However, significant challenges were identified, including inconsistent student responses, limited parental support, peer influence, and reliance on punitive approaches that may not ensure long-term internalization of discipline values. Collaborative and reflective strategies were found to foster deeper student commitment to classroom norms. Conclusion: Teachers play a pivotal role in cultivating student discipline through consistent modeling, reinforcement, and participatory classroom management. Nevertheless, effective discipline education requires sustained collaboration between schools and families, as well as the adoption of more humanistic and reflective pedagogical approaches to ensure long-term character development.